Where the dandelion meets the road: Location determinants of German bioeconomy patents - S. zu Jeddeloh; Sidonia von Proff; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2022)
The paper at hand provides deep insights into the development of the German bioeconomy at the municipality level. The aim was to find out which determinants play a role in the location of bioeconomy patents at the municipality level and to analyze the respective stages of the bioeconomy in the industry life cycle (ILC). Within the three fields of biomass, biotechnology, and biomaterials, subfields were built through a keyword-driven approach to capture the bioeconomy. We conducted a logit regression model using the following data sets: population density, the area of forestry and agriculture, German Federal subsidy data, topic-specific patents and publications, as well as the overall patent and publication activity. The results indicate that the researched bioeconomy fields are in different stages of their life cycles and that they perhaps change the known structure of the life cycles. It appears that bioeconomy patents rather emerge in rural areas, and that there is only a minor influence of the usage of the surrounding landscape. Most of the subfields show a positive reaction to public subsidies. Furthermore, path dependence is strongly influencing the occurrence of bioeconomy patents. Our research can be used by diverse stakeholder groups, especially federal and local politicians as well as scientists, and contribute to the understanding of the bioeconomy on the so far relatively uncommon, but comprehensive level of municipalities.
Keywords: Q57; Q10; R11; 330; bioeconomy; biomass; biotechnology; biomaterials; patents; publications; subsidies; industry life cycle (ILC); regional innovation systems (RIS); municipality; path dependence